The Global Health 50/50 Towards Gender Equality Initiative: GAIN’s performance: 2018-2021 - Haddad, Lawrence (2021)
Lawrence Haddad POLICY SEMINAR Global Food 50/50: Inaugural report on gender, diversity and power in the global food system Co-Organized by IFPRI and Global Health 50/50 OCT 5, 2021 - 08:00 AM TO 09:30 AM EDT